Technique adjustments influence the performance of sprint paddling in competitive male surfers - Sheppard, J. M.; Osborne, M.; Chapman, D. W.; Andrews, M.; McNamara, P. (International Journal of Sports Science and Coaching, 2013)
The present study evaluated what are considered common and contentious differences in paddling technique within the surfing population, across the three distinct categories of: 1) Paddle Stroke length (Reach); 2) Torso Inclination (Chest Position); and 3) Arm Recovery. To assess the differences among paddling techniques, this study employed a within-subjects comparison of sprint paddling kinematic performance differences. Twenty competitive male surfers (19.1±6.8 years, 168.2±11.3 cm, 61.7±13.6 kg) performed 2 maximal trials each of Long vs. Short Reach, Chest Up vs. Down Position, and High vs. Low Arm Recovery during 15 m sprint paddle trials. The sprint paddle efforts were initiated from a stationary, prone lying position, using a horizontal position transducer attached to the rear waistline of each subjects' board-shorts such that kinematic data was obtained for 5 m, 10 m, and 15 m distances, and peak paddling velocity determined. There was no difference observed between Short and Long paddle strokes for any of the distance intervals, nor for peak paddling velocity (p>0.05). For chest position, the Down condition was found to be faster than the Chest Up position for all criterion variables (p=0.01-0.05), with moderate magnitude (d=0.25-0.43). The Low Arm Recovery resulted in superior performance compared to the High Arm Recovery (p=0.02-0.04), with low and moderate magnitudes (d=0.19-0.47). Sprint paddling is likely best conducted with the surfer's chest low to the board, without considerable extension through the back, and with a low arm recovery.